2022
DOI: 10.3390/ijms23031475
|View full text |Cite
|
Sign up to set email alerts
|

BMP9-ID1 Signaling Activates HIF-1α and VEGFA Expression to Promote Tumor Angiogenesis in Hepatocellular Carcinoma

Abstract: Since hepatocellular carcinoma (HCC) is a typical hypervascular malignant tumor with poor prognosis, targeting angiogenesis is an important therapeutic strategy for advanced HCC. Involvement of bone morphologic protein 9 (BMP9), a transforming growth factor-beta superfamily member, has recently been reported in the development of liver diseases and angiogenesis. Here, we aimed to elucidate the role of BMP9 signaling in promoting HCC angiogenesis and to assess the antiangiogenic effect of BMP receptor inhibitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Significantly altered pathways included diverse types of cascades that are linked to endothelial cell generation or function such as ElF2, ID1, and mTOR signaling. EIF2 signaling is comprised of several endothelial cell transcription factors and regulates both cell cycle progression and angiogenesis [ 55 57 ], while ID1 signaling activates HIF-1a and VEGF-A to promote tumor angiogenesis in certain cancers [ 58 ]. Concurrently, the mTOR pathway in endothelial cells has been shown to regulate angiogenic sprouting, migration, cytoskeleton reorganization, and signaling events impacting matrix adhesion [ 59 , 60 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Significantly altered pathways included diverse types of cascades that are linked to endothelial cell generation or function such as ElF2, ID1, and mTOR signaling. EIF2 signaling is comprised of several endothelial cell transcription factors and regulates both cell cycle progression and angiogenesis [ 55 57 ], while ID1 signaling activates HIF-1a and VEGF-A to promote tumor angiogenesis in certain cancers [ 58 ]. Concurrently, the mTOR pathway in endothelial cells has been shown to regulate angiogenic sprouting, migration, cytoskeleton reorganization, and signaling events impacting matrix adhesion [ 59 , 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…4c ) . Intriguingly, ID1 signaling was recently shown to activate VEGF-A to promote angiogenesis [ 58 ]. Taken together, in our organoid system there is substantial evidence of increased angiogenic potential in SCZ compared to CTRL, a possible effect of enriched ID1, ElF2 and mTOR pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, BMP9 has been shown to promote the growth of HCC cell lines [50]. Another study found that BMP9 induces angiogenesis via the ID1 signaling axis, and therefore acts as a pro-tumorigenic [51].…”
Section: Discussionmentioning
confidence: 99%
“…Livers 2023, 3, FOR PEER REVIEW 9 lines [50]. Another study found that BMP9 induces angiogenesis via the ID1 signaling axis, and therefore acts as a pro-tumorigenic [51]. Together, these previous studies have indicated the complexity of the BMP system in diseased livers, since individual members of the large BMP protein family can even have opposite effects on critical pathological steps of chronic liver diseases.…”
Section: Institutional Review Board Statementmentioning
confidence: 98%
“…VEGFR2 is expressed in almost all ECs and is activated by binding of VEGFA, B, C, or D. VEGFA is the most critical ligand among these VEGFs. The binding of VEGFA/VEGFR2 leads to a phosphorylation cascade that triggers downstream cellular signaling pathways, including the PI3K/AKT and RAF/MAPK pathways, thereby resulting in ECs proliferation and migration, and the formation of branches of new blood vessels necessary for rapid tumor growth and metastasis 14 , 15 . Furthermore, the permeability of the newly formed vessels usually increases, thus forming areas of high interstitial pressure and severe hypoxia or necrosis, which further promote HCC progression and angiogenesis 16 .…”
Section: Angiogenic Factorsmentioning
confidence: 99%